Investigasi Material Baru Sebagai Pengganti Part Dies Import - Moch. Chamim; Kaleb Priyanto; Dio Agusta P (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2019)
The Special Material Used As a Stamping Process (Dies) Cutting Tool is Currently Needed by the Manufacturing Industry. Many Companies Use Import Materials As Part of the Production Process Even Though Many of the Same Material Properties Are Found in the Domestic Market. the Purpose of This Study is to Observe Changes in the Microstructure and Improvement in Mechanical Properties of Imported Dies and Skd-11 Steel Components As a Replacement. This Research Was Carried Out by Heating Skd-11 Steel Specimens to Austenitic Temperature of 850oc with Holding Time for 1 Hour and 2 Hour Then Cooled with Water. the Specimens That Have Been Subjected to Heating and Cooling Are Then Subjected to Rigorous and Microstructure Testing. Microstructure Observation Results Show That the Longer the Holding Time, There Are More Martensitic Carbide Content Which Can Result in Harder Material. the Results of Skd-11 Steel Hardness Testing Without Heat Treatment (224.3 Hv), with a Holding Time for 1 Hour (559.7 Hv), and for 2 Hours (580.9 Hv). the Hardness Test Results Show That with Increasing Holding Time the Hardness Value Will Rise and Reach the Highest Value at a Holding Time of 2 Hours (580.9 Hv). the Conclusion From the Data Shows That Skd-11 Steel Experienced an Increase in Violence but Could Not Match the Hardness Value of Imported Dies Materials.